2023
DOI: 10.1088/2053-1583/acba2c
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliablity, magnetism, energy storage and stability of metal thiophosphate nanosheets made in liquid medium

Abstract: The family of antiferromagnetic layered metal hexathiohypo diphosphates, M2P2S6 represents a versatile class of materials, particularly interesting for fundamental studies on magnetic properties in low dimensional structures, and yet exhibiting great potential for a broad variety of applications including catalysis, energy storage and conversion, and spintronics. In this work, three representatives of this family of 2D materials (M = Fe, Ni, and Mn) are exfoliated in the liquid phase under inert conditions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…However, the emission already disappears at approximately 100 K, which is below the Neél temperature of LPE NiPS 3 confirmed by our previous study. 51 Thus, we identify an additional effect from thermal heating on the excitonic luminescence in LPE NiPS 3 , beyond the reported connection to the presence of antiferromagnetic order. The blue shift of the subpeaks (A, B, and C see Supporting Information Figure 6a) upon cooling is typical of the temperature-dependent bandgap energy 52 change in semi-conductors.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…However, the emission already disappears at approximately 100 K, which is below the Neél temperature of LPE NiPS 3 confirmed by our previous study. 51 Thus, we identify an additional effect from thermal heating on the excitonic luminescence in LPE NiPS 3 , beyond the reported connection to the presence of antiferromagnetic order. The blue shift of the subpeaks (A, B, and C see Supporting Information Figure 6a) upon cooling is typical of the temperature-dependent bandgap energy 52 change in semi-conductors.…”
Section: Resultsmentioning
confidence: 54%
“…The luminescence from Peak I vanishes as temperature increases (Figure c and Supporting Information Figure 6a), which is in line with previous reports and can be considered as a result of the antiferromagnetic-to-paramagnetic phase change in the NiPS 3 thin films. However, the emission already disappears at approximately 100 K, which is below the Néel temperature of LPE NiPS 3 confirmed by our previous study . Thus, we identify an additional effect from thermal heating on the excitonic luminescence in LPE NiPS 3 , beyond the reported connection to the presence of antiferromagnetic order.…”
Section: Resultsmentioning
confidence: 91%
“…As an example, pressure-driven compression has been reported to change the magnetic properties, as well as to cause transitions from a semiconductor to a metal in MnPS 3 and MnPSe 3 . 63,64 Moreover, several TEM studies 60,62,65,66 on fewlayer TMPTs proved that few-layer TMPTs can be successfully prepared. Furthermore, strong modifications of the structure and properties of few-layer transition metal phosphorus trisulfides caused by electron irradiation were reported.…”
Section: Introductionmentioning
confidence: 97%
“…Theoretical and experimental studies showed the possibility of tailoring the properties of these materials by different stimuli. As an example, pressure-driven compression has been reported to change the magnetic properties, as well as to cause transitions from a semiconductor to a metal in MnPS 3 and MnPSe 3 . , Moreover, several TEM studies ,,, on few-layer TMPTs proved that few-layer TMPTs can be successfully prepared. Furthermore, strong modifications of the structure and properties of few-layer transition metal phosphorus trisulfides caused by electron irradiation were reported. ,, A predominant removal of sulfur in few-layer TMPTs by electron irradiation in the low-voltage regime (i.e., 30–80 kV) in TEM was observed. ,, Calculations revealed that the elastic knock-on displacement threshold of S is significantly lower compared to, for instance, MoS 2 or MoSe 2 . , Thus, elastic damage plays a significant role in investigating transition metal phosphorus trisulfides in TEM above 50 kV. , Further, inelastic damage channels cause the primary removal of S in TMPTs as well below the knock on threshold .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation